Wine evolution during bottle aging, studied by 1H NMR spectroscopy and multivariate statistical analysis. (February 2019) - Cassino, Claudio; Tsolakis, Christos; Bonello, Federica; Gianotti, Valentina; Osella, Domenico
Abstract: The study of wine evolution during bottle aging is an important aspect of wine quality. Ten different red wines ( Vitis vinifera ) from Piedmont region were analysed 3 months after bottling and after a further 48 month conservation in a climate controlled wine cellar kept at a constant/controlled temperature of 12 °C. Two white wines ( Vitis vinifera ) were included in this study for comparison purposes. White wines were analysed 3 months after bottling and after further 24 months of bottle aging in the same climate controlled wine cellar. Metabolite changes during this period were evaluated using 1 H NMR spectroscopy combined with statistical analysis. Metabolite variations due to wine aging were minimal compared to those that resulted from a different wine type and wine geographical origin. Therefore, it was necessary to remove this source of variability to discriminate between fresh and refined samples. The storage at low and controlled temperature for 2 or 4 years permitted a slow but progressive evolution of all wines under investigation. 1H NMR spectroscopy, implemented with statistical data analysis, allowed identifying and differentiating wine samples from the two aging stages. In most wines, a decrease in organic acids (lactic acid, succinic acid and tartaric acid) and an increase in esters (ethyl acetate and ethyl lactate) was observed. Catechin and epicatechin decreased during aging in all wines while gallic acid increased in almost all red wines. Graphical abstract: Unlabelled Image Highlights: Red and white wines were differentiated according to aging through NMR. Contribution of different NMR spectrum regions to wines differentiation was assessed. Statistical data analysis allowed identifying metabolites changing during aging.